THE EFFECT OF FINANCIAL PERFORMANCE ON LQ45 SHARE RETURN IN INDONESIA STOCK EXCHANGE - nikmah, ida nur; handini, sri (Ekspektra : Jurnal Bisnis dan Manajemen, 2020)
This research was conducted with the aim to find out and analyze the effect of simultaneous return on assets, return on equity, debt to equity ratio, debt to assets ratio, earnings per share, and price earning ratio on LQ45 stock returns on the Indonesia Stock Exchange. This study uses a quantitative approach. Based on the porposive sampling technique, the companies that met the research criteria were 17 LQ45 companies on the Indonesia Stock Exchange. The data used are financial statements for the period 2015-2017. Data analysis techniques are using multiple linear regression, F test, and t test.Based on the results of the study note that simultaneous return on assets, return on equity, debt to equity ratio, debt to assets ratio, earnings per share, and price earnings ratio does not affect stock returns, this is evidenced by the results of testing with the F test that shows the significance value is greater than 0.05 which is equal to 0.187. Return On Assets does not have a significant effect on stock returns because the significance value of the t test is greater than 0.05 which is 0.767. Return On Equity does not have a significant effect on stock returns because the significance value of the t test is greater than 0.05 which is equal to 0.489. Debt to Equity Ratio has no significant effect on stock returns because the significance value of the t test is greater than 0.05 which is equal to 0.935. Debt to Assets Ratio does not have a significant effect on stock returns because the significance value of the t test is greater than 0.05 which is 0.593. Earning Per Share has a significant effect on stock returns because the significance value of the t test is greater than 0.05 which is equal to 0.025. Price Earning Ratio has no significant effect on stock returns because the significance value of the t test is greater than 0.05 which is equal to 0.336.